UMA COLCHA DE SABERES ANTIRRACISTAS NAS PERCEPÇÕES DE DOCENTES NEGRAS DE UMA ESCOLA PÚBLICA DE AÇAILÂNDIA - MARANHÃO - SANTOS, Leciane Costa dos (2025)
This dissertation aims to understand Anti-Racist Education through the perceptions and experiences of Black female teachers working in a public school in Açailândia, Maranhão. It highlights how their life trajectories and pedagogical practices contribute to confronting racism within the school environment. Developed within the framework of the Professional Master's Program in Education and Educational Practices (PPGEPE), the research seeks to describe the personal experiences of these educators, their strategies for coping with racial prejudice, and how such experiences may foster Anti-Racist Education. The study is situated in a public school in Açailândia, Maranhão. It is guided by the central research question: “How can Anti-Racist Education be understood through the perceptions of Black female teachers in a public school in Açailândia – Maranhão?”, along with other supporting questions that address the implementation of Law 10.639/2003, the formation of Black women as teachers in the face of racism, and the contributions of their intertwined life and professional narratives to contemporary debates on anti-racist practices. The participants are two Black female teachers whose narratives were recorded through oral and written productions, using conversation circles and semi-structured interviews. The study included two collective and two individual meetings. Theoretical support draws from autobiographical research in education and studies centered on Black women educators, while the methodological approach is grounded in the historical struggles of the Black population and the advancement of Law 10.639/2003 within school settings. As a practical outcome, an Instructional Guide was developed to support Anti-Racist teaching in elementary education. The findings reveal that the pursuit of Anti-Racist Education is a continuous and collective process, and that the lived experiences and voices of Black female teachers are essential for building school environments that embrace diversity. By valuing narratives, acknowledging symbolic violence, and promoting critical thinking, Anti-Racist Education supports the development of empathetic, conscious individuals committed to equity, fostering belonging, self-esteem, and full citizenship.